LEGAL MECHANISMS FOR RECOVERY OF DAMAGE CAUSED TO BUSINESS BY WAR - Moroz, Viktor; Abrazhevych, Daria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: the article is devoted to the analysis of realities and prospects of development of normative regulation of the mechanism of recovery of damage caused to business by war. Methods of research: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, etc. Results: the conceptual aspects of normative regulation of the mechanism of recovery of damage caused by the war, problems of introduction of the appropriate legal mechanism of recovery of damage caused by the war in the legislation of Ukraine, genesis of normative regulation of economic and legal relations, the comparative analysis of normative regulation of this aspect of economic and legal relations in Ukraine. Discussion: an analysis of the normative regulation of the mechanism of recovery of damage caused by the war. In Ukraine, the war with the russian federation has been going on for nine months, as a result of which a significant number of various property objects and complexes were destroyed or damaged, which significantly complicated, and sometimes made it impossible to do business, destroying the fixed assets on which such a business was built. Logically, the question arises about the responsibility of guilty persons for the damage caused to business by war. Difficult and debatable is both the identification of guilty persons, and, in fact, bringing them to justice and the actual recovery of the damage caused by them (damage caused). Sometimes, for example, in the case of the occupation of certain territories, it is also difficult to determine and confirm the real amount of damage caused by the war, due to the complexity of access to destroyed (destroyed) property. The relevant aspects determine the need for a systematic study of the normative regulation of legal mechanisms for the recovery of damage caused to business by war, not only for the purpose of developing legal science, but also, provided that the necessary methodological framework is developed, the legislation is improved and the practice of its application. Normative regulation of mechanisms for the recovery of damage caused to business by war is carried out using a system of legal norms with a complex hierarchy, which is in an active state of formation. Issues of jurisdictional immunity, identification of guilty persons, establishment and confirmation of real losses and lost benefits caused to business as a result of armed aggression, causal relationship between the damage caused and actions or inaction of guilty persons are complex issues that lie simultaneously in the plane of international law and economic and procedural law of Ukraine and require theoretical study with subsequent consolidation in judicial practice. It is seen that the topic of finding effective mechanisms for the recovery of damage caused to business by war requires further study with the reflection of the results of such processing in regulatory acts.